Model identification and real-time implementation of a linear parameter–varying control scheme on lab-based inverted pendulum system. (January 2021) - Barkat, Anila; Hamayun, Mirza Tariq; Ijaz, Salman; Akhtar, Saleem; Ansari, Ejaz Ahmad; Ghous, Imran
To research the tendencies of immediate change in the scheduled parameters, a linear parameter–varying control strategy is made in real time for lab-based inverted pendulum system. An adjusted and observing virtual instrument is designed in LabVIEW to construct this mechanism. To obtain the transient response data, a step response is transmitted by virtual instrument to the inverted pendulum by which model of inverted pendulum is identified. System model depicts its characteristics, so this model is employed in designing controller. To improve the performance and robustness, linear parameter–varying controller is created to deal with parameter distinctions. Furthermore, the effectiveness of this designed robust controller is checked by integrating on hardware system. The discovered model is checked by evaluating the presented approaches in real time and simulation outcomes with traditional controller as proportional–integral–derivative controller and linear–quadratic regulator.